Innovations and developments in single cell protein: Bibliometric review and patents analysis - Ribeiro, Gislane Oliveira; Rodrigues, Leticia de Alencar Pereira; Santos, Thiale Borges Silva dos; Alves, João Pedro Santos; Oliveira, Roseane Santos; Nery, Tatiana Barreto Rocha; Barbosa, Josiane Dantas Viana; Soares, Milena Botelho Pereira (Frontiers in Microbiology, 2023)
Global demand for food products derived from alternative proteins and produced through sustainable technological routes is increasing. Evaluation of research progress, main trends and developments in the field are valuable to identify evolutionary nuances. In this study, a bibliometric analysis and search of patents on alternative proteins from fermentation processes was carried out using the Web of Science and Derwent World Patents Index™ databases, using the keywords and Boolean operators “fermentation” AND “single cell protein” OR “single-cell protein.” The dataset was processed and graphics generated using the bibliometric software VOSviewer and OriginPro 8.1. The analysis performed recovered a total of 360 articles, of which 271 were research articles, 49 literature review articles and 40 publications distributed in different categories, such as reprint, proceedings paper, meeting abstract among others. In addition, 397 patents related to the field were identified, with China being the country with the largest number of publications and patents deposits. While this topic is largely interdisciplinary, the majority of work is in the area of Biotechnology Applied Microbiology, which boasts the largest number of publications. The area with the most patent filings is the food sector, with particular emphasis on the fields of biochemistry, beverages, microbiology, enzymology and genetic engineering. Among these patents, 110 are active, with industries or companies being the largest depositors. Keyword analysis revealed that the area of study involving single cell protein has included investigation into types of microorganisms, fermentation, and substrates (showing a strong trend in the use of agro-industrial by-products) as well as optimization of production processes. This bibliometric analysis provided important information, challenges, and trends on this relevant subject.